Efforts to improve the understanding of blood circulation concepts through the guided discovery learning model - Mohamad Zakia Mathori (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The problem in this research is how the application of the Guided Discovery Learning Model can improve the understanding of science concepts in elementary school students? Purpose To determine the application of the Guided Discovery Learning Model can improve understanding of science concepts in elementary school students. The object of this research is the fifth grade students of SDN Sidaurip 04 Gandrungmangu. The data collection technique was carried out systematically with standard procedures, namely, learning outcome data was taken through tests at the end of each cycle and observation of student participation. The data were analyzed using quantitative and qualitative analyzes of the formative test results. Then, the results of the calculations were consulted with the success criteria, to determine whether they were complete or not. Based on the results of the evaluation test from the first and second cycles, an increase in learning completeness was obtained. In the first cycle achieved learning outcomes with 66.67% completeness. In the second cycle the completeness of learning outcomes was 88.89%. Based on the findings and results obtained in the study, it can be concluded that, through the Guided Discovery Learning Model, it can improve understanding of the science concept of elementary school students